Phase I study of vorinostat in combination with isotretinoin in patients with refractory/recurrent neuroblastoma: A new approaches to Neuroblastoma Therapy (NANT) trial. Issue 7 (30th March 2018) - Pinto, Navin; DuBois, Steven G.; Marachelian, Araz; Diede, Scott J.; Taraseviciute, Agne; Glade Bender, Julia L.; Tsao‐Wei, Denice; Groshen, Susan G.; Reid, Joel M.; Haas‐Kogan, Daphne A.; Reynolds, C. Patrick; Kang, Min H.; et al.
Abstract: Background: Vorinostat combined with retinoids produces additive antitumor effects in preclinical studies of neuroblastoma. Higher systemic exposures of vorinostat than achieved in pediatric phase I trials with continuous daily dosing are necessary for in vivo increased histone acetylation and cytotoxic activity. We conducted a phase I trial in children with relapsed/refractory neuroblastoma to determine the maximum tolerated dose (MTD) of vorinostat on an interrupted schedule, escalating beyond the previously identified pediatric MTD. Methods: Isotretinoin (cis‐13‐retinoic acid) 80 mg/m 2 /dose was administered by mouth twice daily on days 1–14 in combination with escalating doses of daily vorinostat up to 430 mg/m 2 /dose (days 1–4; 8–11) in each 28‐day cycle using the standard 3 + 3 design. Vorinostat pharmacokinetic testing and histone acetylation assays were performed. Results: Twenty‐nine patients with refractory or relapsed neuroblastoma were enrolled and 28 were evaluable for dose escalation decisions. Median number of cycles completed was two (range 1–15); 11 patients received four or more cycles. Three patients experienced cycle 1 dose‐limiting toxicities. A total of 18 patients experienced grade 3/4 toxicities related to study therapy. The maximum intended dose of vorinostat (430 mg/m 2 /day, days 1–4; 8–11) was tolerable and led to increased histone acetylation in surrogate tissues when compared to lower doses of vorinostat ( P = 0.009). No objective responses were seen. Conclusions: Increased dose vorinostat (430 mg/m 2 /day) on an interrupted schedule is tolerable in combination with isotretinoin. This dose led to increased vorinostat exposures and demonstrated increased histone acetylation. Prolonged stable disease in patients with minimal residual disease warrants further investigation.